2018
DOI: 10.1016/j.abrep.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and tobacco use among methadone maintenance patients in Vietnamese rural mountainside areas

Abstract: IntroductionThe expansion of methadone maintenance treatment (MMT) program requires more data about the factors affecting the effectiveness of treatment, especially behavioral data such as smoking and alcohol use among patients. This study aimed to examine the prevalence of tobacco and alcohol consumption and identify related factors among MMT patients in the Vietnamese rural mountainside.MethodsWe interviewed 241 MMT patients in two clinics in Tuyen Quang, a mountainous province in Vietnam. Patients were aske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
2
15
1
Order By: Relevance
“…Similarly, a study conducted in Kombolcha town, Ethiopia, found that current alcohol drinkers had an increased chance of developing common mental distress or MD than non-alcohol drinkers [ 50 ]. Alcohol counselling program combined with social and family support plays an essential role in alcohol control and prevention of psychiatric comorbidity [ 52 ]. Regular khat use was also found to be a risk factor for MD in the current study (both studies conducted in Jimma and Kombolcha supported this finding) [ 42 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study conducted in Kombolcha town, Ethiopia, found that current alcohol drinkers had an increased chance of developing common mental distress or MD than non-alcohol drinkers [ 50 ]. Alcohol counselling program combined with social and family support plays an essential role in alcohol control and prevention of psychiatric comorbidity [ 52 ]. Regular khat use was also found to be a risk factor for MD in the current study (both studies conducted in Jimma and Kombolcha supported this finding) [ 42 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…We divided the smoking status of participants into 3 types: Current smokers, former smokers, and never-smokers [16]. A current smoker was an adult who had smoked at least 100 cigarettes in his or her lifetime and had smoked in the last 30 days.…”
Section: Health Risk Behaviorsmentioning
confidence: 99%
“…Since the introduction of the first pilot MMT clinic in 2008, the Vietnamese government has scaled up the delivery of these programs in nationwide as a core component of the HIV reduction strategy in Vietnam [9]. These programs have been recognized that reduced psychological distress [10], stigma [11,12], alcohol and tobacco use [13], economic vulnerability [14], risky sexual behaviors [15], and unemployment [16].…”
Section: Introductionmentioning
confidence: 99%
“…Higher QoL is closely associated with higher level of MMT adherence and higher likelihood of community reintegration via improving workability [19][20][21]. However, most of the studies were conducted in urban and rural settings, while a lack of evidence was documented in mountainous areas, where the accessibility of health care services among drug users is constrained [10,11,13,15,22,23]. Therefore, this study aimed to assess QOL, mental disorders and their associated factors amongst people using drugs over the course of 12-month MMT in Vietnamese mountainous provinces.…”
Section: Introductionmentioning
confidence: 99%